Evaluation of performance, combustion and emission characteristics of blends of soybean biodiesel in a single cylinder diesel engine: An experimental approach - Karn, Rupesh Lal; Sharma, Shahil; Maharjan, Lasata; Bajagain, Gagin; Jyakhwo, Samjhana; Subedi, Sushila; Palikhel, Laxman (Kathmandu University Journal of Science Engineering and Technology, 2025)
This experimental study evaluates the performance, combustion, and emission characteristics of soybean biodiesel blends (10–40% v/v) in a single-cylinder diesel engine. Soybean methyl ester (SME) was produced via single-stage alkaline transesterification due to low free fatty acid content (<2%). Tests were conducted on a variable compression ratio engine (17:1, 1500 rpm) at varying brake power loads. GC-MS analysis confirms a fatty acid methyl ester (FAME) profile dominated by methyl linoleate (48.42%) and methyl oleate (32.35%). Engine testing revealed that B30 optimized performance parameters, increasing brake thermal efficiency by 11.94% and reducing brake-specific fuel consumption by 5.41% relative to diesel. Emission analysis demonstrated that B20 achieved maximal reductions: CO$_2$ (3.5%), NO (19.2 %), HC (18.97 %), and NO$_x$ (18.93 %). Combustion characteristics showed marginal decreases in peak cylinder pressure (≤3.5%) and net heat release (≤6.18%) for most blends, attributable to SME’s lower calorific value (33.54–41.66 MJ/kg vs. 42.5 MJ/kg for B0). The study establishes B20–B30 blends as optimal for balancing engine efficiency with emission mitigation, affirming soybean biodiesel’s viability in conventional diesel engines without modification.